Modification of hole transport layer to enhance the performance of polymer solar cells / Saqib Rafique - Saqib, Rafique (2017)
Despite the fact that development of organic solar cells (OSCs) is rapidly accelerating as the new need of green energy sources, they continue taking backstage roll in growing markets of various photovoltaic technologies due to their limited efficiency and stability. One of the challenges in obtaining the high performance of OSCs is an inefficient charge extraction and transportation to the electrodes, in particular, inability of new generation of donor polymers to obtain Ohmic contacts between the electrodes and the photo-active layer. Poly (3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) is the current state of the art interfacial material used to reduce these contact barriers between the photo-active layer and indium tin oxide (ITO) electrode. However, PEDOT:PSS as a hole transport layer (HTL) also favors device degradation due to its hygroscopic and acidic nature, resulting in severe device instability. Combination of metal oxides and/or graphene oxide (GO) along with PEDOT:PSS to form a composite HTL is expected to compliment the drawbacks of any of the individual materials. This dissertation is primarily focused on identifying and addressing the stability and degradation issues associated with bulk heterojunction (BHJ) solar cells. In particular, vanadium pentaoxide (V2O5), and/or graphene oxide (GO) along with the PEDOT:PSS were studied and device based on organic-inorganic hybrid HTL were fabricated and characterised. The first part of the work is devoted to the stability and degradation issues. Layer by layer degradation study of BHJ OSCs with pristine PEDOT:PSS HTL was performed to identify the factors affecting device efficiency and stability. It was demonstrated that indium diffusion from ITO anode and oxygen ingress from atmosphere are some of the major causes of device instability, which affect the morphological, optical, compositional and photovoltaic characteristics of the OSCs. Another task of this work was to fabricate and study the normal architecture BHJ OSCs based on hybrid HTL consisting of PEDOT:PSS along with V2O5, and/or GO, and compare the device performance with that of pristine PEDOT:PSS. In this context, applicability of V2O5 incorporated in PEDOT:PSS aqueous suspension to form organic-inorganic HTL in BHJ OSCs was shown. The resultant devices were tested on merits of their efficiency and operational stability. Our results indicate that V2O5 could be a simple addition into the PEDOT:PSS layer to overcome its stability and degradation issues leading to an effective HTL in BHJ OSCs. The last part of the work demonstrates the applicability of GO as an HTL material and further challenges were discussed. Firstly, the GO concentration was optimised, thereafter, optimised concentration of GO was used along with PEDOT:PSS in GO/PEDOT:PSS double decked HTL structure. The devices were tested on merits of their power conversion efficiency (PCE), reproducibility, stability and compared with the devices with individual GO or PEDOT:PSS HTLs. It was shown that performance of the device with GO/PEDOT:PSS HTL is significantly improved than that of devices with individual PEDOT:PSS or GO HTLs. The current work is based on highly reproducible, solution processable and cost effective fabrication techniques.